News, discourse, and significance in the story of the merits of women’s deception - Mohamed, Dr. Donia Talib (Thi Qar Arts Journal, 2022)
I chose to write this research from the Book of Advances and Oppositions to Al-Jahiz (1), the chapter that talks about the deception of women - they mentioned that Al-Hajjaj bin Yusuf was thinner, one night, so he sent to the son of the village, so he said: Women and their actions) - and on their ability to deceive men with gentle tricks that indicate the virtue of intelligence and breadth of mind. Among the deceitfulness of women is this trick that "Jamila" defrauded from the men who had taken her to herself and asked her for what she could not afford, so she knew how to take her right from them and win the honor of showing her without them.